The safety and efficacy of high-speed train transport for critical children: a retrospective propensity score matching cohort study - Zhe Zhao (Nature Portfolio, 2021)
Abstract It is widely acknowledged that efficiency of pediatric critical care transport plays a vital role in treatment of critically-ill children. In developing countries, most critically-ill children were transported by ambulance, and a few by air, such as a helicopter or fixed airplane. High-speed train (HST) transport may be a potential choice for critically-ill children to a tertiary medical center for further therapy. This is a single-center, retrospective cohort study from June 01, 2016 to June 30, 2019. All the patients transported to the Pediatric Intensive Care Unit (PICU) of PLA general hospital were divided into two groups, HST group and ambulance group. The propensity score matching method was performed for the comparison between the two groups. Finally, a 2:1 patient matching was performed using the nearest-neighbor matching method without replacement. The primary outcome was hospital mortality. Secondary outcomes included duration of transport, transport cost, hospital stay, and hospitalization cost. A total of 509 critically-ill children were transported and admitted. Of them, 40 patients were transported by HST, and 469 by ambulance. The hospital mortality showed no difference between the two groups (p > 0.05). The transport distance in the HST group was longer than that in the ambulance group (1894.5 ± 907.09 vs. 902.66 ± 735.74, p < 0.001). However, compared to the HST group, the duration of transport time by ambulance was significantly longer (p < 0.001). No difference in vital signs, blood gas analysis, and critical illness score between groups at admission was noted (p > 0.05). There was no death during the transport. There was no difference between groups regarding the transport cost, hospital stays, and hospitalization cost (p > 0.05). High-quality tertiary medical centers are usually located in megacities. HST transport network for critically-ill children could be established to cover most regions of the country. Without increasing financial burden, HST medical transport can be a potentially promising option to improve the outcomes of critically-ill children in developing countries with developed HST network. Clinical Trial Registration: This study was registered at http://www.chictr.org.cn/index.aspx (chiCTR.gov; Identifier: ChiCTR2000032306).